Anodal tDCS to Right Dorsolateral Prefrontal Cortex Facilitates Performance for Novice Jazz Improvisers but Hinders Experts - Rosen, David S.; Erickson, Brian; Kim, Youngmoo E.; Mirman, Daniel; Hamilton, Roy H.; Kounios, John (Frontiers in Human Neuroscience, 2016)
Research on creative cognition reveals a fundamental disagreement about the nature of creative thought, specifically, whether it is primarily based on automatic, associative (Type-1) or executive, controlled (Type-2) processes. We hypothesized that Type-1 and Type-2 processes make differential contributions to creative production that depend on domain expertise. We tested this hypothesis with jazz pianists whose expertise was indexed by the number of public performances given. Previous fMRI studies of musical improvisation have reported that domain expertise is characterized by deactivation of the right-dorsolateral prefrontal cortex (r-DLPFC), a brain area associated with Type-2 executive processing. We used anodal, cathodal, and sham transcranial direct-current stimulation (tDCS) applied over r-DLPFC with the reference electrode on the contralateral mastoid (1.5mA for 15 min., except for sham) to modulate the quality of the pianists’ performances while they improvised over chords with drum and bass accompaniment. Jazz experts rated each improvisation for creativity, aesthetic appeal, and technical proficiency. There was no main effect of anodal or cathodal stimulation on ratings compared to sham; however, a significant interaction between anodal tDCS and expertise emerged such that stimulation benefitted musicians with less experience but hindered those with more experience. We interpret these results as evidence for a dual-process model of creativity in which novices and experts differentially engage Type-1 and Type-2 processes during creative production.